The Practice of Telecommuting: A Fresh Perspective - Franco GANDOLFI; Gary OSTER (Revista de Management Comparat International)
Telecommuting has been a popular practice for an increasing number of firms and governmental bodies over the past decade or more. This research paper reviews antecedents, implementation considerations, known consequences, barriers, and recommendations that need to be determined prior to the adoption of telecommuting practices. The paper demonstrates that the phenomenon of telecommuting is the result of historical, sociological, and technological shifts and advancements. While firms have successfully implemented various elements of telecommuting practices, challenges along the way have yielded insights and lessons that merit further examination and discussion. This paper asserts that with selected individuals, proper structure, and sufficient feedback mechanisms in place, the adoption of telecommuting has the capacity to strengthen a firm’s bottom line and provide tangible benefit for its employees. As a case in point, online learning, developed in parallel with the growth of telecommuting, yields substantial benefits for employees and the companies in which they serve. For employees, online learning is convenient, accommodates multiple learning styles, and is an engaging learning mechanism. For corporations, online learning encourages cost-effectiveness, uniformity in quality and flexibility, and enhanced cross-cultural and cross-disciplinary communications, all necessary to meet the challenges of the ever-changing global marketplace.